Women showrunners in Spain (2019-2024): Tasks, obstacles and leadership - Del Castillo, Miren Itxaso; Fuentes, Pedro; Iturbe, Andoni (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article focuses on the role of female showrunners in Spain, from the period 2019 to the present. The main objective of the research is to examine whether female showrunners play the same roles as their male counterparts, at a quantitative and qualitative level and to detect their tasks, obstacles and leadership. The methodology is based on semi-structured interviews with five Spanish female showrunners. The conclusions point out that while they are involved in all the tasks, including the choice of the people in charge of the different technical areas or the equipment, the women interviewed are involved in the directing functions more closely related to the script.